Effect of polysaccharide of dendrobium candidum on proliferation and apoptosis of human corneal epithelial cells in high glucose - Li, Qiangxiang (Medicine (Baltimore), 2017)
BACKGROUND: The aim of the study was to observe the effect of polysaccharide of dendrobium candidum (PDC) and high glucose on proliferation, apoptosis of human corneal epithelial cells (HCEC). METHODS: The MTT method was used to screen and take the optimal high-glucose concentration, treatment time, and PDC concentration using HCEC and divide it into 4 groups: control group (C), high glucose group (HG), PDC group, and HG + PDC group. We observed and compared the effect of the 4 groups on HCEC proliferation by MTT, apoptosis by Annexin V-FITC/PI double fluorescent staining and flow cytometry (FCM), and expression of bax mRNA and bcl-2 mRNA by RT-qPCR. RESULTS: Compared with the control group, proliferative activity of HCEC cells was reduced; the cells apoptosis ratio was increased; the expression of bax mRNA was increased, and the expression of bcl-2 mRNA was reduced in the HG group. Proliferative activity of HCEC cells in the PDC group was increased, and the expression of bcl-2 mRNA was increased but that of bax mRNA was decreased. Proliferative activity of HCEC cells in the HG + PDC group was increased, but it could not restore to the normal level; the expression of bax mRNA was significantly decreased but the expression of bcl-2 mRNA was significantly increased. CONCLUSIONS: Our results demonstrate that high glucose can inhibit proliferative activity and induce apoptosis of HCEC. PDC can improve the proliferative activity of HCEC cells under the high glucose environment and reduce the apoptosis of cells by regulating the expression of bax and bcl-2. PDC play a very important role on protecting and repairing of corneal epithelial cells damage in high glucose.